2006
DOI: 10.1007/s11745-006-5087-5
|View full text |Cite
|
Sign up to set email alerts
|

Selective incorporation of docosahexaenoic acid into lysobisphosphatidic acid in cultured THP‐1 macrophages

Abstract: Lysobisphosphatidic acid (LBPA) is highly accumulated in specific domains of the late endosome and is involved in the biogenesis and function of this organelle. Little is known about the biosynthesis and metabolism of this lipid. We examined its FA composition and the incorporation of exogenous FA into LBPA in the human monocytic leukemia cell line THP-1. The LBPA FA composition in THP-1 cells exhibits an elevated amount of oleic acid (18:1n-9) and enrichment of PUFA, especially DHA (22:6n-3). DHA supplemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
35
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 53 publications
4
35
0
Order By: Relevance
“…In alveolar macrophages, BMP predominantly contains n-6 fatty acids, such as linoleic acid (18:2) and arachidonic acid (20:4) ( 75,76 ). Interestingly, DHA (C22:6, n-3) comprises a signifi cant portion of BMP fatty acids in many cell types in drug-induced phospholipidosis, and also in many LSDs ( 22,(70)(71)(72)(73)(77)(78)(79)(80)(81)(82). We also found that DHA was a major fatty acid species in BMP from the brains of mice, cats, and bears with gangliosidosis.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In alveolar macrophages, BMP predominantly contains n-6 fatty acids, such as linoleic acid (18:2) and arachidonic acid (20:4) ( 75,76 ). Interestingly, DHA (C22:6, n-3) comprises a signifi cant portion of BMP fatty acids in many cell types in drug-induced phospholipidosis, and also in many LSDs ( 22,(70)(71)(72)(73)(77)(78)(79)(80)(81)(82). We also found that DHA was a major fatty acid species in BMP from the brains of mice, cats, and bears with gangliosidosis.…”
Section: Discussionmentioning
confidence: 60%
“…C18:1 is a major BMP fatty acid in many cell types (69)(70)(71)(72)(73)(74). In alveolar macrophages, BMP predominantly contains n-6 fatty acids, such as linoleic acid (18:2) and arachidonic acid (20:4) ( 75,76 ).…”
Section: Discussionmentioning
confidence: 99%
“…In steady-state labeling, lymphoblasts were maintained at a density of ,10 6 cells/ml and labeled in complete medium containing 32 Pi (10 mCi/ml) for 3 days at 37jC. CHO cells were seeded in 100 mm diameter dishes and cultured to confluence in complete medium containing 32 Pi (10 mCi/ml) for 1 or 3 days at 33, 37, or 40jC.…”
Section: Radioactive Cell Labelingmentioning
confidence: 99%
“…CHO cells were seeded in 100 mm diameter dishes and cultured to confluence in complete medium containing 32 Pi (10 mCi/ml) for 1 or 3 days at 33, 37, or 40jC. At the end, cells were washed twice with PBS and harvested by centrifugation (lymphoblasts) or scraping (CHO cells).…”
Section: Radioactive Cell Labelingmentioning
confidence: 99%
See 1 more Smart Citation